Evaluating the Influence of Social Media Advertising on E-Commerce Sales - Ilsha, Musani; Malviya, Chirag; Vidani, Jignesh (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
Social media has become a value-adding marketing channel. With the significance of social media for online small businesses and the lack of understanding of this area, this study attempts to investigate the impact of social media marketing on the sales performance of such business. This research analysis the marketing through social media and its impact in E-Commerce sales.